Aspirin-Dependent Effects on Purinergic P2Y1 Receptor Expression - Massimi, Isabella; Alemanno, Laura; Guarino, Maria Luisa; Guerriero, Raffaella; Mancone, Massimo; Ceccacci, Andrea; Frati, Luigi; Angiolillo, Dominick J.; Pulcinelli, Fabio M. (Thrombosis and Haemostasis, 2019)
Chronic treatment with aspirin in healthy volunteers (HVs) is associated with recovery of adenosine diphosphate (ADP)-induced platelet activation. The purinergic P2Y1 receptor exerts its effects via a Gq-protein, which is the same biochemical pathway activated by thromboxane-A2 receptor. We hypothesized that recovery of ADP-induced platelet activation could be attributed to increased P2Y1 expression induced by chronic aspirin exposure. We performed a multi-phase investigation which embraced both in vitro and in vivo experiments conducted in (1) human megakaryoblastic DAMI cells, (2) human megakaryocytic progenitor cell cultures, (3) platelets obtained from HVs treated with aspirin and (4) platelets obtained from aspirin-treated patients. DAMI cells treated with aspirin or WY14643 (PPARα agonist) had a significant up-regulation of P2Y1 mRNA, which was shown to be a PPARα-dependent process. In human megakaryocytic progenitors, in the presence of aspirin or WY14643, P2Y1 mRNA expression was higher than in mock culture. P2Y1 expression increased in platelets obtained from HVs treated with aspirin for 8 weeks. Platelets obtained from patients who were on aspirin for more than 2 months had increased P2Y1 expression and ADP-induced aggregation compared with patients on aspirin treatment for less than a month. Overall, our results suggest that aspirin induces genomic changes in megakaryocytes leading to P2Y1 up-regulation and that PPARα is the nuclear receptor involved in this regulation. Since P2Y1 is coupled to the same Gq-protein of thromboxane-A2 receptor, platelet adaptation in response to pharmacological inhibition seems not to be receptor specific, but may involve other receptors with the same biochemical pathway.
Keywords: aspirin; purinergic receptors; PPARα; platelet reactivity